Select biological characteristics of the mossul bleak Alburnus mossulensis Heckel, 1843 (Actinopterygii: Cyprinidae) in the Ataturk Dam Lake, Turkey - ParmaksÄ±z, Arif; Oymak, Ahmet; Dogan, Necmettin; Unlu, Erhan (Indian Journal of Fisheries, 2018)
Maturity, growth and reproductive characteristics of the mossul bleak Alburnus mossulensis, from Ataturk Dam Lake (Euphrates) were assessed. Maturity composition of the analysed samples varied between age groups I and VII. The ratio of females to males was 1.047:1. Fork length of the samples varied between 40-198 mm and weights were in the range of 0.45-68 g. The regression equations derived for the length-weight relationship was Log W = -5.5531+3.2958 Log FL (r2=0.9593) for females and Log W=-5.3695+3.2112 Log FL (r2=0.9487) for males. Mean condition factor was determined as 1.069 for females and 1.062 for males. Absolute fecundity was established to be between 288 and 3380. The age of sexual maturity was 3 years in females and 2 years in males.